Who are the next entrepreneurs? - Abdullah, Zainal; Griggs, Frank T.; Planisek, Sandra L. (Universiti Utara Malaysia, 1995)
Identifying potential entrepreneurs is important for governments trying to increase the number of small, flexible, job-creating domestic business. Academic research into the personality tendencies of actual and potential entrepreneurs has generated confusing and contradictory results. Current work stresses that motivation, learnable and non-learnable characteristics, might all distinguish future entrepreneurs from the general population. In this study, survey data on the motivation, demographics and learnable characteristics of business students in Malaysia and the United States were used to seek answers to the following questions 1) Do entrepreneurs differ from the general population? 2) Do actual entrepreneurs differ from potential entrepreneurs? and 3) Do entrepreneurs differ across cultures? The results indicate that it is possible to differentiate entrepreneurs from the general public, that actual and potential entrepreneurs do differ and that American and Malaysian entrepreneurs are different.